Factors associated with low birthweight among newborns delivered at term in a tertiary care hospital in Lahore (Journal of Fatima Jinnah Medical University, 2022)
Background: Low birth weight (LBW) is an important risk factor that contributes to mortality of 15-20% of newborn globally. This case-control study was conducted to determine factors associated with low birth weight among new-born delivered at term in obstetrical and gynecological wards of the hospital.Patients and methods: Mothers of 150 low birth weight babies born at term were taken as cases and 150 normal weight babies born at same day, were taken as controls. Mothers were interviewed on using a semi-structured and pretested questionnaire. The data was analyzed on SPSS Version 22.0. A p-value
Keywords: Low birth weight; Socio-demography; Pregnancy; Factors; Term newborns